Robert Duncan’s Long Poem Debates and his Poetics of Grand Collage - Rachel Blau DuPlessis (Sillages Critiques, 2020)
This article examines Robert Duncan’s debates in poetics that distinguish Charles Olson’s long poem The Maximus Poems from his own work in order to understand the function of the poems named “Passages” in Duncan’s oeuvre from 1968 on. The definitions of collage and of Grand Collage for Duncan further illuminate his resistance to the long poem.